SANCTIONS ON MUZAKKI IN THE COMPILATION OF SHARIA ECONOMIC LAW IN THE REVIEW OF MAQASHID SYARIAH JASSER AUDA - Dzaky Adam Thamrin; Nur Chanifah; Siti Rohmah (PT. Radja Intercontinental Publishing, 2026)
This research is based on the existence of Article 684 of the Supreme Court Regulation (Perma) Number 2 of 2008 concerning the Compilation of Sharia Economic Law (KHES) which regulates sanctions for muzakki who do not pay zakat, this provision is not implemented in practice. This condition indicates the incompleteness of the regulation of zakat sanctions resulting in its implementation in Indonesia tending to be understood as a voluntary moral obligation. This phenomenon is reviewed using the framework of the six elements of maqashid sharia proposed by Jasser Auda, namely cognitions, holism, openness and self-renewal, interrelated hierarchy, multi-dimensionality, and purposefulness which are the measures of benefit in Islamic law. The aim is to reveal the problems that exist in the regulation of sanctions for muzakki in Article 684 KHES so that the regulation is not implemented. The method used in this normative legal research is a statutory approach and analyzed descriptively analytically. The results of this study indicate that there are deficiencies in the rules of sanctions for muzakki who do not pay zakat in Article 684 of the KHES, so that the article cannot be implemented. Among them are the inconsistency of norms with fiqh, unfair imposition of sanctions, traditions of how to pay zakat which are factors in the inability of sanctions to be implemented, incomplete formal legal rules in enforcing zakat sanctions, inconsistencies with existing legal realities, ambiguity in the composition of articles which causes confusion in interpreting articles, as well as the non-recognition of KHES sanctions in the hierarchy of laws and regulations, and the unavailability of adequate formal law to realize the benefit.